Studi intervensi keberagaman dan pemberian Makanan Pendamping ASI (MP-ASI) dengan status gizi anak usia 6-24 bulan - Fitrianingsih, Eva; Rachmawati, Rachmawati; Sastri, Sastri (Poltekkes Kemenkes Aceh, 2024)
Background: High rates of undernutrition are strongly associated with feeding practices. Good complementary feeding, including appropriate education to improve with or without food supplements, is very effective in reducing the incidence of stunting in the first two years of life. Inadequate complementary feeding is caused by low food quality and child feeding practices that affect the nutritional status of children where in Aceh Besar District the prevalence of nutritional status of weight-for-age indicators is 5,4% malnutrition and 16,7% underweight (22,1%).Objective: To determine the effect of diversity and complementary feeding on the nutritional status of children aged 6-24 months.Methods: The design of this study is Quasy Experimental using the Wilcoxon test with a pre-post test approach in the case group to see the provision of diversity education and complementary feeding practices with nutritional status aged 6-24 months in Aceh Besar District. The study was conducted in Darul Imarah District, Aceh Besar Regency with a total sample size of 40 people. Results: There was a significant difference before and after the intervention in the case group on children's weight (p = 0,001), energy intake (p = 0,001), carbohydrate intake (p value = 0,003), protein intake (p value = 0,022), fat intake (p value = 0,003), and there was no significant difference in the diversity of complementary foods (p value = 0,001).Conclusion: Children's body weight, energy intake, carbohydrate intake, protein intake, and fat intake were significantly affected after the intervention.